2022
DOI: 10.3389/fimmu.2022.850856
|View full text |Cite
|
Sign up to set email alerts
|

The Give-and-Take Interaction Between the Tumor Microenvironment and Immune Cells Regulating Tumor Progression and Repression

Abstract: A fundamental concern of the majority of cancer scientists is related to the identification of mechanisms involved in the evolution of neoplastic cells at the cellular and molecular level and how these processes are able to control cancer cells appearance and death. In addition to the genome contribution, such mechanisms involve reciprocal interactions between tumor cells and stromal cells within the tumor microenvironment (TME). Indeed, tumor cells survival and growth rely on dynamic properties controlling pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 121 publications
0
38
0
Order By: Relevance
“…Finally, we normalized the expression profiles of 597 samples with complete follow-up information (Figure 1E). Previous references have reported the ability of CAFs to recruit immunosuppressive cells, so we performed immunofluorescence staining using immunofluorescence in patients with primary tumors and in patients with recurrent tumors (39). Interestingly, there was a recruitment of Treg cells (green) around the CAF cells (pink) in patients with primary tumors (Figure 2A), especially in the recurrent samples, where a larger number of Treg cells clustered to the prominent part of the CAF cells (Figure 2B).…”
Section: Cancer-associated Fibroblasts and Stromal Score Could Be Con...mentioning
confidence: 86%
“…Finally, we normalized the expression profiles of 597 samples with complete follow-up information (Figure 1E). Previous references have reported the ability of CAFs to recruit immunosuppressive cells, so we performed immunofluorescence staining using immunofluorescence in patients with primary tumors and in patients with recurrent tumors (39). Interestingly, there was a recruitment of Treg cells (green) around the CAF cells (pink) in patients with primary tumors (Figure 2A), especially in the recurrent samples, where a larger number of Treg cells clustered to the prominent part of the CAF cells (Figure 2B).…”
Section: Cancer-associated Fibroblasts and Stromal Score Could Be Con...mentioning
confidence: 86%
“…These alterations consist of the recruitment of fibroblasts, migration of immune cells, stroma remodeling, and progression of tumor-specific vasculature [ 61 ]. The prognosis of cancer is correlated with immune cell infiltration and activation, thus the TME, which is composed of diverse infiltrating immune and stromal cells, may greatly impact therapy response and clinical outcome, in addition to playing a crucial role in cancer etiology and progression [ 62 , 63 ]. This study integrated multiple prediction methods to assess the association between EZH2 expression and the abundance of infiltrating immune cells in PCa in order to better determine the impact of the tumor immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Low percentages of basophils (0.4%) were located in the immune infiltrate of human non-small cell lung cancer (NSCLC) tumors (262). Basophils have been identified in the [263][264][265], which are often a prominent part of the immune cell landscape of the TME. However, in chronic inflammation, the exposure of basophils to certain cytokines, such as IL-33, may induce the polarization of lung macrophages to M2-like phenotype characterized by the expression of anti-inflammatory genes Clec7a, Arg1, Itgax.…”
Section: Basophils In Solid Cancersmentioning
confidence: 99%
“…It remains unclear what the exact function basophils mediate in the TME, yet emerging evidence points to their capacity to secrete IL-4 and IL-13 as playing a potential role. For example, mouse and human studies have shown that basophils, by secreting these cytokines, facilitate the development/expansion of M2-like monocytes/macrophages ( 227 , 263 265 ), which are often a prominent part of the immune cell landscape of the TME. However, in chronic inflammation, the exposure of basophils to certain cytokines, such as IL-33, may induce the polarization of lung macrophages to M2-like phenotype characterized by the expression of anti-inflammatory genes Clec7a, Arg1, Itgax .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation